Quantitative analysis of pellets on beaches of the São Paulo coast and associated non-ingested ecotoxicological effects on marine organisms - Izar, G. M.; Morais, L. G. [UNESP]; Pereira, C. D.S.; Cesar, A.; Abessa, D. M.S. [UNESP]; Christofoletti, R. A. (Elsevier, 2019)
We evaluated the densities of plastic pellets on beaches along the coast of São Paulo State in Brazil in order to establish a relationship between their spatial distribution and their distance from the main source of pellets. We hypothesized that pellets would be concentrated close to their main source (in this case, the Port of Santos). We also tested whether beached pellets could induce toxicity in water and sediment samples, as well as whether pellet color, sample site (beach), and pellet density were correlated with toxicity. We observed a decreasing gradient of pellet density along the São Paulo coast, with higher densities detected within Santos Bay, which is close to the Port of Santos. Beached pellets induced water-based toxicity in the sea urchin Lytechinus variegatus and the copepod Nitocra sp. at high densities but were not capable of producing toxicity at environmentally realistic densities.
Keywords: Coastal impact; Microplastics; Plastic pellets; Pollutants; Sources; Toxicity